HORMONES AND PROSPECTS: PSYCHOLOGICAL AND ENDOCRINE CHARACTERISTICS OF CHRONIC ANXIETY AND STRESS AMONG SCHOOLCHILDREN AND STUDENTS OF THE “THREE RUSSIAS” - Kozlov, A.I.; Kornienko, D.S.; Vershubsky, G.G.; Otavina, M.L.; Negasheva, M.A. (Perm Federal Research Centre Journal, 2016)
The aim of the study is to describe the complex psychological and endocrine characteristics of stress reaction in groups of schoolchildren and students living in places with different degrees of urbanization. The study involved 983 students and schoolchildren from Moscow, Perm, Kudymkar, and settlement Beloevo (Perm Krai). The results: 1) the transition to university has a stress-effect that affects the endocrine and psychological level, 2) the highest level of stress reactions is typical for students of a big city compared to students of a megapolis or a small town, 3) the highest level of psychological and endocrine reactions was found for schoolchildren from a small town. The differences in the manifestations of stress reactions are related to the size of a place and are likely to be caused by chronic stress as a reaction to a large crowd of people in a megapolis and a big city.